Biomass-based carbon materials for CO2 capture: A review. (February 2023) - Quan, Cui; Zhou, Yingying; Wang, Jiawei; Wu, Chunfei; Gao, Ningbo
Abstract: Carbon capture and sequestration technologies are essential to reduce CO2 emissions which are responsible for global warming. Carbon-based materials can play an important role in the reduction of CO2 emissions. These materials are normally produced from biomass through technologies such as pyrolysis and hydrothermal carbonization. The type of biomass feedstock and biomass conversion conditions can significantly affect the textual properties and surface chemistry of the carbon materials. Various modification methods such as material activation or N-doping can improve the properties of carbon materials to obtain better CO2 capture effects. This review summarizes recently reported research in the areas of using biomass-based materials for CO2 capture. The technologies of biomass conversion to carbon materials and modification of the carbon materials are critically analyzed. Meanwhile, the mechanisms of the CO2 capture process and research of different modification carbon materials for CO2 capture are also discussed. Finally, potential future research directions are suggested to promote carbon capture using biomass-based materials. Highlights: The preparation technologies of carbon materials and influencing factors are discussed. Traditional and emerging carbon material modification methods are summarized. Recent researches of carbon materials for CO2 capture and its capture mechanisms are discussed. Future research directions and challenges in carbon materials for CO2 capture are discussed.